Meaning in Artificial Intelligence Linguistics. - Al-Shams, Khaled Hower (International Journal on Humanities & Social Sciences, 2025)
This study aims to establish the distinct specialisation of ''Artificial Intelligence Linguistics'' within the broader field of interlinguistics. It is based on the integration and compatibility between linguistics and artificial intelligence. The researcher explores several core topics, with a particular focus on the concept of meaning The central research question posed is: *Has the concept of meaning been addressed in the literature of artificial intelligence, which examines the relationship between language and AI as a science that harmonises with various other fields, including linguistics, psychology, applied mathematics, and neuroscience*? To address this, the research begins by defining the concept of artificial intelligence and then introduces the notion of *artificial intelligence linguistics, distinguishing it from *computational linguistics, while highlighting its interdisciplinary nature. The study then investigates the concept of meaning within artificial intelligence linguistics, coining the term *intelligent meaning*, in analogy with established concepts such as psychological, social, and structural meanings. This *intelligent meaning* is rooted in the use of language within computer programs and is manifested in various forms, including: *Spoken language *Written language *Morphological structures *Grammatical constructions *Lexical elements The research further explores the characteristics of intelligent meaning, its representation in AI literature, and the types of problems it addresses within AI contexts. Finally, it identifies specific domains where meaning plays a significant role in artificial intelligence applications.